2013
DOI: 10.1164/rccm.201301-0079oc
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Drug-Resistant Pathogens in Community-acquired and Healthcare-associated Pneumonia

Abstract: The clinical profile of HCAP was different from that of CAP. However, physicians can predict drug resistance in patients with either CAP or HCAP by taking account of the cumulative number of the risk factors. Clinical trial registered with https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&recptno=R000004001&language=E ; number UMIN000003306.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
319
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(352 citation statements)
references
References 44 publications
11
319
4
1
Order By: Relevance
“…Scoring systems to identify patients with MDR infections, including MDR P. aeruginosa, are available but limited in their overall ability to predict MDR infection. 23,36,37 A number of novel methods aimed at improving the early identification of pathogens and related antibiotic susceptibilities are also entering the diagnostic arena. Such technological advances offer a strategy that could potentially maximize the administration of appropriate antibiotic therapy while minimizing unnecessary antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring systems to identify patients with MDR infections, including MDR P. aeruginosa, are available but limited in their overall ability to predict MDR infection. 23,36,37 A number of novel methods aimed at improving the early identification of pathogens and related antibiotic susceptibilities are also entering the diagnostic arena. Such technological advances offer a strategy that could potentially maximize the administration of appropriate antibiotic therapy while minimizing unnecessary antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several other risk factor models have been developed as outlined in Table 1 [7][8][9][10][11][12]. These algorithms were locally developed by investigators, often with the assistance of outside experts, with the primary goal of improving upon the identification of patients with pneumonia attributed to antibiotic-resistant bacteria.…”
mentioning
confidence: 99%
“…With the emergence of new broad spectrum antibiotics, this separation may become unnecessary. While Pseudomonas infections are more likely to develop in patients with structurally damaged lungs, including chronic obstructive pulmonary disease (especially in the setting of prior antibiotic exposure), cerebrovascular disease and during the second episode of ventilator-associated pneumonia [16], MRSA pneumonia seems to preferentially affect elderly nursing home residents with previous hospitalizations and patients having received courses of antibiotics or tube feeds [10]. Moreover, it is important to recognize that, even in countries with low rates of MDR pneumonia, the presence of immunosuppression significantly increases the likelihood of infection with MDR Gram-negative bacteria and MRSA [12].…”
mentioning
confidence: 99%
“…For example, communityacquired pneumonia (CAP) drug-resistant pathogens (DRPs) are more commonly found in patients with healthcare-associated risk factors. Shindo et al [11] demonstrated that independent risk factors for DRPs in both patients diagnosed with CAP and healthcare-associated pneumonia (HCAP) included prior hospitalization, immunosuppression, previous antibiotic use, use of gastric acid-suppressive therapy, tube feeding, and nonambulatory status. These are similar to independent risk factors identified in a clinical score for assessing the risk of resistant pathogens in patients with pneumonia presenting to the emergency department [12].…”
mentioning
confidence: 99%